PENINGKATAN PERILAKU SOSIAL SISWA MELALUI PENERAPAN KLARIFIKASI NILAI DALAM PEMBELAJARAN SISWA DI SMAN 1 TANGERANG - Nurleila Nurleila; Dafyar Eliadi H; Hardjito S Darmojo (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
This study aims to improve students' social behavior through Improving Students' Social Behavior through the Application of Value Clarification in Student Learning at SMAN 1 Tangerang. The improvement is focused on four aspects of values, namely obedience to worship, tolerance, caring and responsibility. This research is a classroom action research which was conducted in three cycles. The subject of the research was class XI students totaling 26 students. The collaborators in this study were the XI grade teacher as the executor of the action and the researcher as the observer. Data collection was done through observation, interviews, field notes and document analysis. Data analysis was carried out qualitatively with techniques developed by Miles and Huberman. The results showed that the learning process of civic education subjects with the application of value clarification techniques can improve students' social behavior in the value aspects of obedience to worship, tolerance, care and responsibility. Learning actions are carried out by clarifying values tailored to civic education subject matter, by applying question and answer models, contextual children's stories, case analysis and group discussions to train cooperation, mutual respect and understanding of others. The increase can be observed in the positive behavior of students with proportions: 1) obedience to worship, cycle I 41.35%, cycle II 50.48% and cycle III 71.15%; 2) tolerance, cycle I 39.90%, cycle II 52.88% and cycle III 74.99%; 3) caring, cycle I 41.15%, cycle II 50.38%, and cycle III 71.54%; 4) responsibility, cycle I 38.46%, cycle II 59.61% and cycle III 72.31%.The increase in student behavior is balanced by an increase in student learning outcomes in each cycle, cycle I student learning outcomes reached an average of 62, cycle II an average of 69 and cycle III 77.5.The improvement in learning outcomes is shown by students' seriousness and responsibility in doing and completing tasks from the teacher. Keywords: Social behavior, Value clarification technique, Civics learning.